2013
DOI: 10.1128/jvi.02886-12
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rabies Vaccine Based on a Recombinant Parainfluenza Virus 5 Expressing Rabies Virus Glycoprotein

Abstract: 8 PFU of rPIV5-RV-G showed a 50% survival rate, which is comparable to the 60% survival rate among mice inoculated with an attenuated rabies vaccine strain, recombinant LBNSE. This is first report of an orally effective rabies vaccine candidate in animals based on PIV5 as a vector. These results indicate that rPIV5-RV-G is an excellent candidate for a new generation of recombinant rabies vaccine for humans and animals and PIV5 is a potential vector for oral vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Currently, kennel cough vaccines are mass produced by major veterinary vaccine companies. Fourth, a PIV5-vectored vaccine has been shown to be efficacious in animals (28)(29)(30)(31)(32). In our recent studies, we have found that a single-dose intranasal (i.n.)…”
mentioning
confidence: 99%
“…Currently, kennel cough vaccines are mass produced by major veterinary vaccine companies. Fourth, a PIV5-vectored vaccine has been shown to be efficacious in animals (28)(29)(30)(31)(32). In our recent studies, we have found that a single-dose intranasal (i.n.)…”
mentioning
confidence: 99%
“…PIV5 can infect humans and animals without causing any known symptoms or diseases (3,4). It has been used as a vector for vaccine development (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It induces virus-neutralizing antibody and protects animals against subsequent RV infection [1,5,26]. As G is the major antigen of RV, various vaccines expressing G alone such as DNA-based rabies vaccines and live recombinant vectors have successfully elicited strong protective immune responses [6,8,28,29]. A modified G may induce a stronger immune reaction: administration of a DNA vaccine expressing ERA G with R333Q resulted in a higher VNA than the unmodified G [16].…”
Section: Discussionmentioning
confidence: 99%
“…Two weeks after the third vaccination, blood was collected for assay of NA to CDV (a) and RV (b). RV NA titer was converted to international units (IU) by comparison with a WHO standard serum Virus Genes RV G [6,8]. CDV also has shown its potential as an effective vaccine vector for RV [27].…”
Section: Discussionmentioning
confidence: 99%